Digital money study in the term and the concept, structure, and relationships = النقود الرقمية دراسة في المصطلح والمفهوم والبنية والعلاقات - Saleh, Abdulmajid Obaid Hasan; bAHMI, Abdulrahim bahami (KPBKL Publication House, 2021)
In the shade of the rapid pace of events in the world today, from the price fluctuations and the lack of investment opportunities. with continued technological development and large investors shaking on digital currency markets with the aim of becoming rich and gets quick profits. thus, we had to spotlight into digital money due to its economic significance. This paper aims to illustrate the concept, nature, and characteristics of electronic money as a virtual and easily traded digital currency, whereby this paper sheds light on the fiduciary characteristic of money and thus addressing the impact of money generation on digital currencies and through anatomize the collected texts and then analyzed, the paper found that if the digital currencies legalized and allowed to be traded in various global markets. This could eliminate the phenomenon of inflation and centralization and might expand the scope of circulation. This study used the descriptive and analytical approach, as it is the appropriate approach to study terms and concepts, characteristics, and their contents.